(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Studies on volume and pressure derivatives of dielectric constants of ionic crystals are useful to make a critical test of the theories of dielectric polarization and interionic forces operative in these crystals. Measurements of first, second and third order pressure derivatives of static or low frequency dielectric constant ε0 have been performed for a number of ionic crystals. These experiments make use of these terminal geometric capacitance (TTGC) techniques. The details of experimental method based on TTGC measurements have been given by Lowndes and Martin. The TTGC method is better than the old immersion method mainly in two respects. First it is quicker method and secondly it does not use high dielectric constant liquids which can prove troublesome. In fact the liquid-solid surface interactions change the dielectric constants by several percent. Among the various measurements based on TTGC the results obtained by Fontanella et alfor alkali halides may be considered to be most accurate. These investigators have assigned an uncertainty of only ± 0.2 for first derivatives of ε0. On the other hand the uncertainties reported by other workers [20-26 ]are of the order of ± 5.The results obtained by Fontanella et al have subsequently been corroborated by Bertels and Smith[40]. In fact the high accuracy achieved is due in part to the use of higher order terms to describe the variation of ε0 with pressure and in part to the improved experimental techniques. Andeen et al have measured the pressure derivatives of ε0of alkaline earth fluoride using the same experimental method.They report an uncertainty of ± 0.01 for the first order pressure derivatives of ε0 for CaF2,SrF2 and BaF2.Their results are in very good agreement with other investigations[40-54].The TTGC method has also been used to measure the temperature and pressure dependences of the dielectric constants of semiconductors.